Enhanced plasticity of the oxide scales by in-situ formed Cr2O3/Cr heterostructures for Cr-based coatings on Zr alloy in 1200 °C steam. (15th May 2021) - Liu, Haiyong; Feng, Yajie; Li, Peng; Shi, Xiaoguang; Zhu, Han; Shu, Jie; Huang, Qing; Ge, Fangfang; Huang, Feng
Highlights: An in-situ formed Cr2 O3 /Cr heterostructure that enhanced the plasticity of scales. To show the deformation behavior in the oxide scales under superimposed stresses. To simulate the stress and strain in the oxidized by the finite element method. To discuss the stress mechanisms of generation and relief for the oxide scales. Abstract: The mechanical maintenance of oxides scales was studied for the chromium (Cr) coated zirconium (Zr) alloy coupons that proceeded oxidation in the 1200 °C steam. During the oxidation process, Cr/CrAlSiN coatings evolved into a structure of a thin and high-quality oxides scale growing over a thick Cr-rich layer, which retained a long-term structural integrity and barrier effect. Moreover, multiple toughening mechanisms could operate in the oxidized specimens when subjected to superimposed stresses. The finite element simulation revealed that the thin scale would generate less growth stress and the thick Cr-rich layer would effectively relieve the stress.